Analisa Perbandingan Metode Aras Dan Vikor Dalam Pengangkatan Jabatan Pegawai Pada Samsat Medan Selatan - Jordan Ebenezer Purba (STMIK Budi Darma, 2022)
Employees are one of the supporting factors for companies and agencies, because they have qualified employees, according to the qualifications and criteria needed by the company, then the company can develop and move forward in the future, there are no South Medan Samsat employees who need appropriate employees to work in a company or agency. South Medan Samsat offers a problem that aims to direct employees on each subject and incompatibility with the work they have. In the appointment of a position in a company or agency by using a system decision by using the comparison of the ARAS method and the VIKOR method, the ARAS method is a comprehensive framework of thinking methods considering the hierarchical process which is then carried out a method used for ranking criteria, calculating weights to calculate a criterion in determine and use the VIKOR method with a decision-making method that works by looking at the closest solution/alternative as an approach to the ideal solution in ranking. From the final results of the ARAS and VIKOR calculations, the employee who got the highest rank was Karimun with a score of 2.19 and became a worthy employee and deserved to be appointed as a branch head, while the employee with the lowest rank was Riri with a final score of -1.84 and became an employee who did not deserve to be an employee.